Cartografias esquizofônicas - Camanho, Ícaro Tavares Capelo (2019)
This work deals with the relationship among the ethical problems sighted in a schizophonic soundscape and its possibilities of creating sonic territorialities. How to listen and to think the activity of organizating sounds – which has been over time reduced to music and musicians – as a machine that operates a passage to already existing and possible territories? How has it been agencied, in diverse situations, a creative resistance which has always done a reappropriation of tools for another purposes, redistributing to another fluxes the activity of listening? An essay at thinking the counter-work of creating sonic lines of flight as musical critique itself: the moment when music seeks another rhythms than those of compulsory labor, of a sedentarized social and subjective life. Extending the experimentations to non-sonic forces, improvising arrangements of gambiarras; pursuing intensities, attempting to return the listening (to) the body (to) the world.